2016
DOI: 10.1152/japplphysiol.00024.2016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of high-intensity interval training and moderate-intensity continuous training on endothelial function and cardiometabolic risk markers in obese adults

Abstract: We hypothesized that high-intensity interval training (HIIT) would be more effective than moderate-intensity continuous training (MICT) at improving endothelial function and maximum oxygen uptake (V̇o2 max) in obese adults. Eighteen participants [35.1 ± 8.1 (SD) yr; body mass index = 36.0 ± 5.0 kg/m(2)] were randomized to 8 wk (3 sessions/wk) of either HIIT [10 × 1 min, 90-95% maximum heart rate (HRmax), 1-min active recovery] or MICT (30 min, 70-75% HRmax). Brachial artery flow-mediated dilation (FMD) increas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
139
2
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 146 publications
(153 citation statements)
references
References 60 publications
(137 reference statements)
7
139
2
5
Order By: Relevance
“…For example, Sawyer et al . observed that MICT sessions resulted in an energy expenditure ~33% higher than that of HIIT; in a study by Kong et al . , the energy expenditure of the MICT sessions was ~102% higher than that of the HIIT sessions.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…For example, Sawyer et al . observed that MICT sessions resulted in an energy expenditure ~33% higher than that of HIIT; in a study by Kong et al . , the energy expenditure of the MICT sessions was ~102% higher than that of the HIIT sessions.…”
Section: Introductionmentioning
confidence: 93%
“…In some of these studies, the analyses compared training methods that presented a significant difference in energy expenditure between the sessions (26,27). For example, Sawyer et al (28) observed that MICT sessions resulted in an energy ex-penditure~33% higher than that of HIIT; in a study by Kong et al (29), the energy expenditure of the MICT sessions was~102% higher than that of the HIIT sessions. Thus, review studies must consider analyses that included isocaloric protocols only (30).…”
Section: Introductionmentioning
confidence: 99%
“…Interventions were conducted for 10.4 ± 3.1 weeks (range 5-16 weeks), and the mode of exercise was matched for HIIT and MICT interventions in all studies. Cycle ergometer was the most common modality (seven studies (24,25,27,30,32,34,35)), followed by treadmill running (six studies (23,26,28,29,31,33)).…”
Section: Studies Included In the Reviewmentioning
confidence: 99%
“…All data for whole-body fat levels (N = 11 studies) were drawn from studies applying either DXA (seven studies (24,25,28,31,32,34,35)) or BIA (four studies (23,26,30,33)). Six studies reported whole-body lean mass (four studies using DXA (27,28,34,35) and two studies using BIA (26,30)), four studies reported trunk fat values (three studies using DXA (25,27,35) and one using BIA (30)) and one CT study provided visceral fat as a measure (33).…”
Section: Studies Included In the Reviewmentioning
confidence: 99%
See 1 more Smart Citation